Antiviral treatment improves disrupted peripheral B lymphocyte homeostasis in chronic hepatitis B virus-infected patients. (November 2013) - Sun, Haibo; Lv, Juan; Tu, Zhengkun; Hu, Xiaoli; Yan, Hongqing; Pan, Yu; Xu, Damo; Lian, Zhexiong; Chi, Xiumei; Niu, Junqi
Disruption of peripheral blood B-cell homeostasis and variation of surface receptors occur with certain infections and autoimmune diseases. However, the impact of antiviral therapy on B-cell alteration during chronic hepatitis B (CHB) infection remains unclear. Our study aims to document the effects of B-cell alteration in CHB patients treated with tenofovir or adefovir. A total of 21 CHB patients and 10 healthy donors were recruited into the study. We identified B-cell subsets by flow cytometry and observed changes in the B-cell repertoire of CHB patients upon tenofovir or adefovir antiviral treatment. The total and percent of B cells and CD5 + B-cell subsets were significantly increased in CHB patients compared to healthy donors. Total and percent of CD5 + B cells gradually decreased following the diminution of the HBV DNA load after tenofovir and adefovir treatment. Upon tenofovir treatment, the percent of memory CD27 + B cells was increased but the absolute number declined, whereas naïve CD27− B cells declined in both percent and absolute number. In the adefovir treatment group, neither naïve nor memory B cells were altered by the treatment. Furthermore, CHB patients displayed higher levels of activation markers (CD69 and CD24) and trended towards restored B-cell homeostasis after antiviral treatment. In conclusion, disrupted B-cell homeostasis is an important feature of CHB patients and is partially restored after control of viral replication by antiviral treatment. B-cell antiviral immunity is improved by restoring B-cell homeostasis and activation.